Gerromorpha (Insecta: Hemiptera: Heteroptera) from the state of Rio Grande do Norte, northeastern Brazil, including a new synonymy - Canejo, Rafael P. R.; Melo, Alan Lane De; Rodrigues, Higor D. D. (Zootaxa, 2023)
A list of Gerromorpha species collected from 2016 to 2023 in the State of Rio Grande do Norte, northeastern Brazil, is presented. Previously, only five species had been recorded from this state. In the present study, based on the compilation of data and new collections, 27 species are recorded from the state, of which 23 represent new records. These species belong to 17 genera and five families: Brachymetra Mayr, 1865; Cylindrostethus Fieber, 1861; Halobates Eschscholtz, 1822; Halobatopsis Bianchi, 1896; Husseyella Herring, 1955; Limnogonus Stål, 1868; Microvelia Westwood, 1834; Neogerris Matsumura, 1913; Ovatametra Kenaga, 1942; Rheumatobates Bergroth, 1892 (Gerridae); Lipogomphus Berg, 1879 (Hebridae); Hydrometra Latreille, 1797 (Hydrometridae); Mesovelia Mulsant & Rey, 1852 (Mesoveliidae); Paravelia Breddin, 1898; Platyvelia Polhemus & Polhemus, 1993; Rhagovelia Mayr, 1865; Stridulivelia Hungerford, 1929 (Veliidae). All collected species are illustrated, and their distributions in the state of Rio Grande do Norte are represented in maps. Also, Neogerris celeris (Drake & Harris, 1934) is proposed here as a junior synonym of N. lotus (White, 1879); the lectotype of the latter is designated.